Hashimoto’s thyroiditis and nanophthalmos in Gabriele-de Vries syndrome: a case report - Huang, Hui; Zhang, Dongguang; Yang, Yu; Yang, Li; Chai, Yong (Frontiers in Endocrinology, 2025)
BackgroundGabriele-de Vries syndrome (GADEVS, OMIM 617557) is a rare autosomal dominant disorder caused by pathogenic variants in the YY1 gene. This report describes a case of GADEVS with concurrent Hashimoto’s thyroiditis (HT) and nanophthalmos, a previously unreported association.Case presentationWe present a case of a 9-year-5-month-old girl who was admitted to the Pediatric Endocrinology Outpatient Clinic due to an asymptomatic neck lump and multiple malformations.Physical examination revealed mild facial dysmorphism, strabismus, an enlarged thyroid gland, and elongated fingers. Laboratory findings showed: thyroid-stimulating hormone (TSH): 68.98 μIU/mL (reference range: 0.27–4.2 μIU/mL); free thyroxine (FT4): 7.51 pmol/L (reference range: 12–22 pmol/L); anti-thyroid peroxidase antibodies:>600IU/mL (reference range: 0–34 IU/mL). Ultrasonography revealed that the left thyroid lobe measured 38 × 11 × 12 mm, the right lobe 39 × 11 × 13 mm, and the isthmus had a thickness of 3.2 mm. Ocular axial measurements confirmed nanophthalmos, and cognitive assessments indicated mild cognitive impairment. Whole-exome sequencing identified a novel heterozygous YY1 mutation (c.385del), resulting in a frameshift variant (p.D129Ifs*127). Levothyroxine replacement therapy successfully corrected the hypothyroidism. After three years of treatment, the patient exhibited: a height increase of 20.3 cm, and an improvement in height percentile from the 10th to the 25th percentile.ConclusionHypothyroidism has been reported in four previous cases (12%) of GADEVS, but autoimmune thyroiditis has not been documented. This suggests that thyroid dysfunction in GADEVS may be associated with underlying immune dysfunction and warrants further evaluation. In the present case, we identified a mutation in the YY1 gene, which is associated with nanophthalmos and may underlie the ocular abnormalities such as strabismus and hyperopia. Clinically, children with GADEVS should undergo comprehensive assessments of thyroid function, thyroid autoantibodies, and ophthalmologic status to facilitate early diagnosis and treatment.